2014
DOI: 10.1158/1535-7163.mct-14-0599
|View full text |Cite
|
Sign up to set email alerts
|

A Chemically Defined Trifunctional Antibody–Cytokine–Drug Conjugate with Potent Antitumor Activity

Abstract: The combination of immunostimulatory agents with cytotoxic drugs is emerging as a promising approach for potentially curative tumor therapy, but advances in this field are hindered by the requirement of testing individual combination partners as single agents in dedicated clinical studies, often with suboptimal efficacy. Here, we describe for the first time a novel multipayload class of targeted drugs, the immunocytokine-drug conjugates (IDC), which combine a tumor-homing antibody, a cytotoxic drug, and a proi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 71 publications
0
27
0
Order By: Relevance
“…It has recently been shown that certain cytotoxic agents can mediate an immunogenic tumor cell death [44,45]. In addition, certain immunostimulatory agents (e.g., antibody-cytokine fusion proteins, immunological check-point inhibitors) may potently synergize with some cytotoxic agents [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that certain cytotoxic agents can mediate an immunogenic tumor cell death [44,45]. In addition, certain immunostimulatory agents (e.g., antibody-cytokine fusion proteins, immunological check-point inhibitors) may potently synergize with some cytotoxic agents [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic behaviour was thought to be due to dying cells having increased immune-stimulatory power. This is called an IDC (immunocytokine drug conjugate) but the IC 50 s need to be matched as the dose can only be achieved by a single molecule [103]. This format was exceptionally potent at around 0.5 mg/kg in an F9 teratocarcinoma model.…”
Section: Antibody Fragments -Quick and Nimble Adcs? 341 Fab And Sinmentioning
confidence: 99%
“…A high-affinity human anti-ED-A monoclonal antibody F8 has been generated targeting tumor neovasculature in vivo (Villa et al 2008). Based on antibody F8 several potent anti-cancer biopharmaceuticals have been developed such as immunocytokines F8-IL13 (Hess and Neri 2015) and F8-IL2 (Pretto et al 2014) and immunocytokine drug conjugate F8-IL2-SS-DM1 (List et al 2014). On the other hand, splicing of FN1 towards producing the isoform with CS1 exon was up-regulated in isoform percentage in the majority of HCC samples.…”
Section: Discussionmentioning
confidence: 99%